Near cut-off wavelength operation of resonant waveguide grating biosensors - Balint Kovacs; Fabio Aldo Kraft; Zsolt Szabo; Yousef Nazirizadeh; Martina Gerken; Robert Horvath (Scientific Reports, 2021)
Abstract Numerical simulations and analytical calculations are performed to support the design of grating-coupled planar optical waveguides for biological sensing. Near cut-off and far from cut-off modes are investigated, and their characteristics and suitability for sensing are compared. The numerical simulations reveal the high sensitivity of the guided mode intensity near the cut-off wavelength for any refractive index change along the waveguide. Consequently, it is sufficient to monitor the intensity change of the near cut-off sensing mode, which leads to a simpler sensor design compared to those setups where the resonant wavelength shift of the guided mode is monitored with high precision. The operating wavelength and the sensitivity of the proposed device can be tuned by varying the geometrical parameters of the corrugated waveguide. These results may lead to the development of highly sensitive integrated sensors, which have a simple design and therefore are cost-effective for a wide range of applications. These numerical findings are supported with experimental results, where the cut-off sensing mode was identified.